Psikologi Umum: Memahami Proses Mental dan Perilaku Manusia dalam Perspektif Ilmiah - Ufairah, Atikah Salsabila Fajari; Astuti, Indah; Indramaya, Selpi (Educational Guidance and Counseling Development Journal, 2024)
Psikologi Umum: Memahami Proses Mental dan Perilaku Manusia dalam Perspektif IlmiahTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//